Penerapan Algoritma C4.5 Dalam Mengukur Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Program Studi - Joko Saputro; Asruddin Asruddin; Alexius Ulan Bani; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In an effort to improve the quality of one's work, an assessment can be carried out. Because with the assessment, an evaluation of the level of quality of a person's work can be carried out. At a university there are many study programs. Where one of the study programs at the university is the informatics engineering study program. In carrying out their duties and responsibilities, the campus makes efforts to improve the quality of work, the leadership evaluates by evaluating the quality of work of the staff at the university. In measuring the quality of work of the staff working in the Study Program, the leadership conducts an assessment of the study program. In conducting the assessment by measuring the level of student satisfaction with the Study Program. Based on this study, it was concluded that PUAS students towards the services of the Study Program.